Web-based Graduate Education in Rural Nursing Case Management - Marietta Stanton; Carolyn Crow; Ruby Morrison; Diane J. Skiba; Todd Monroe; Gina Nix; Valeria Gooner (Rural Nurse Organization; Binghamton University, 2012)
The decreasing supply of advanced practice nurses continues to be a problem that plagues America, especially in rural regions. It has been suggested that nurse educators aggressively recruit potential graduate students and provide "easy access" for nurses presently living and practicing in rural areas. Web-based or on-line courses not only improve access to graduate education for rural nurses but also provide for high quality teaching and learning experience for both students and faculty. The purpose of this study was to examine what students in a web-based graduate program in rural nursing case management and faculty perceive are the advantages and disadvantages of web-based learning. In this descriptive study, interviews and a written survey were used for data collection. The sample included six faculty teaching in the graduate nursing program at the time of data collection and 29 former students enrolled or graduated from the program. Findings revealed by students included difficulties with computer technology, unclear expectations for coursework, and lack of socialization as disadvantages. Students identified teacher advocacy and accessibility through distance education as advantages of the program. Faculty identified access as the major advantage. Disadvantages identified by faculty included lack of socialization for students, faculty workload, and a need for ongoing faculty development.